2017
DOI: 10.1039/c6cs00745g
|View full text |Cite
|
Sign up to set email alerts
|

Physical principles for DNA tile self-assembly

Abstract: DNA tiles provide a promising technique for assembling structures with nanoscale resolution through self-assembly by basic interactions rather than top-down assembly of individual structures. Tile systems can be programmed to grow based on logical rules, allowing for a small number of tile types to assemble large, complex assemblies that can retain nanoscale resolution. Such algorithmic systems can even assemble different structures using the same tiles, based on inputs that seed the growth. While programming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 53 publications
0
82
0
Order By: Relevance
“…We found that saccharide coatings on the supramolecular nanostructures enabled us to visualize their morphologies with the aid of saccharide-bindingb iotools such as lectins and an aptamer without significant interference with the imaging of DNA microspheres by conventionals taining techniques with an intercalator. Researchc oncerning DNA nanostructures [5] and the supramolecular nanostructures of peptide derivatives [17] is rapidly expanding. The present findings provide valuable insight into the design of new complex materials consisting of DNAand peptide-based supramolecular nanostructures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that saccharide coatings on the supramolecular nanostructures enabled us to visualize their morphologies with the aid of saccharide-bindingb iotools such as lectins and an aptamer without significant interference with the imaging of DNA microspheres by conventionals taining techniques with an intercalator. Researchc oncerning DNA nanostructures [5] and the supramolecular nanostructures of peptide derivatives [17] is rapidly expanding. The present findings provide valuable insight into the design of new complex materials consisting of DNAand peptide-based supramolecular nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…The programmables equences and predictable interactions of DNA allow av ariety of DNA nanostructures with controlled sizes ands hapes to be constructed. [5] Moreover,a mphiphilic lipid-based vesicles have been interlaced with the DNA nanostructures to construct, for example, active nanoporess panning the lipid bilayer membranes of vesicles [6] or to control the stability, [7a,b] size, [7c] and morphology [7d] of vesicles.T hisc learly demonstrates the orthogonalc oexistenceo fD NA nanostructures and lipid-based vesicles. Except for thesef ew examples, the orthogonal coexistence of DNA nanostructures with supramolecular nanostructures obtained by self-assemblyo fa rtificially designed, synthetic molecules has yet to be explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…DNA tiles, which designed based on an immobile DNA branched junction, a stable analog of the Holliday intermediate from genetic recombination, have been used as versatile nanoscale building blocks for the “bottom‐up” synthesis of fully addressable lattices and structures . Most of them are based on the hybridization of a specific sticky end through a careful thermal annealing process . This assembly process is advantageous in that it provides high flexibility, but the passive self‐assembly by periodic hybridization of the sticky ends might limit the finite size control and site‐selective labeling of the assembled structures.…”
mentioning
confidence: 99%
“…These dsDNA tiles are often constructed from only a few oligos and through control of their shape and interaction interfaces, 2D and 3D crystals will self-assemble as shown in Figure 2.2. Assembly of useful structures can be difficult as careful control of design and experimental parameters and an increasing number of unique tiles are necessary to assemble large, error-free, tiles with programmed addressability 30 .…”
Section: Scaling Dna Self-assemblymentioning
confidence: 99%
“…Several methods of scaling DNA self-assembly to industry relevant dimensions are being investigated and include self-assembly of large DNA crystals from entirely unique ssDNA strands 29 , small dsDNA tile assembly 30 , DNA origami self-assembly using multiple scaffold strands or scaffold strands larger than the standard m13mp18 ssDNA 31 , and tiling of m13mp18 based DNA origami 17 . Each method presents its own advantages and disadvantages.…”
Section: Scaling Dna Self-assemblymentioning
confidence: 99%